Effect of Aqueous Leaf Extract of Ficus benghalensis on Nociception and Sedation in Rats - Deraniyagala, S.A.; Ratnasooriya, W.D.; Perera, P.S. (My University, 2002)
The aim of this study was to investigate the effects of aqueous leaf extract (WE), of Ficus benghalensis Linn. (Family: Moraceae) on nociception and sedation using male rats. Different doses of the WE (0,125, 250, 500 or 1000 mg/kg) were orally administered and one hour later the effects on nociception and sedation were determined using hot plate and tail flick test and rat hole board technique. The WE had no analgesic or sedative effect but exhibited marked hyperalgesic action determined in the hot plate test indicating that this effect was mediated supraspinally. The hyperalgesic activity was dose-dependent with an ED50 value of 585.7 mg/kg. The WE extract was well tolerated even after subacute treatment; with no sums of overt toxicity, hepatotoxicity, haematoxicity, stress or motor impairments. Further, WE did not induce any aversive behaviour characteristic of painlike syndrome.
Keywords: Ficus benghalensis; Nociception; Hyperalgesia; Analgesia; Sedation